2015
DOI: 10.3109/13697137.2015.1058354
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a 10-week Nordic walking training program on the level of GH and LH in elderly women

Abstract: Nordic walking for postmenopausal women with overweight and obesity led to favorable hormonal responses, as well as improvement in muscle integrity and nutritional and inflammatory states, suggesting chronic, regular exercise as an effective tool in protecting against menopause-related catabolic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
2
6
0
1
Order By: Relevance
“…Please, note the indicative changes of HDL level (Figure 2C) that show alignment with the extent of PA (Figure 1A). The recorded anti-parallel changes of HDL and LDL cholesterol levels are in harmony with literature data (Hagner-Derengowska et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Please, note the indicative changes of HDL level (Figure 2C) that show alignment with the extent of PA (Figure 1A). The recorded anti-parallel changes of HDL and LDL cholesterol levels are in harmony with literature data (Hagner-Derengowska et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…showed a reduction in TG, LDL-C, and an increase in HDL-C after 12 weeks of a NW training program in premenopausal, perimenopausal, and postmenopausal women, with the exception of HDL-C levels in postmenopausal women. Similar findings were reported by Hagner-Derengowska et al34 after a 10-week NW program in their study comprised of 32 postmenopausal women with excessive weight or obesity. However, those authors did not compare the effects of NW and CW training programs.…”
supporting
confidence: 91%
“…Participation in NW may also affect LDH levels. Hagner-Derengowska et al [21] reported on 32 post-menopausal women showed that LDH activity in its participants decreased signi cantly after a cycle of 10-week NW trainings (184.3 vs 175.7 IU/l).…”
Section: Lactate Dehydrogenase (Ldh)mentioning
confidence: 98%